2014
DOI: 10.1038/sj.bdj.2014.1007
|View full text |Cite
|
Sign up to set email alerts
|

Food references in UK children's magazines — an oral health perspective

Abstract: Objective: Children's magazines are popular in the United Kingdom, but their content is poorly regulated. Consequently food and beverages high in fat, salt and sugar (HFSS), detrimental to oral and wider health, make unrestricted appearances. The study aim was to assess the amount of HFSS food and drink children are exposed to whilst reading magazines; with particular focus on foods containing NME's (non-milk extrinsic sugars) due to their known cariogenic properties, and foods with low pH due to their erosive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The current children's food marketing environment is largely comprised of high-calorie, low-nutrient food products designed and promoted by food companies to specifically appeal to children [12,13].A strong evidence base supports the association between exposure to unhealthy foods and a negative impact on children's dietary attitudes, preferences, and consumption [9][10][11]14]. Research in Canada and other economically developed countries has also shown that food and beverage companies target children across multiple media, including print media (e.g., magazines), [15,16] television, [17] digital media (e.g., viewed in social media, on desktop computers, on smartphones, etc. ), [18][19][20][21] and out-of-home media (e.g., billboards, signs, transit shelters) [22] as well as other settings such as schools and retail environments [13,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The current children's food marketing environment is largely comprised of high-calorie, low-nutrient food products designed and promoted by food companies to specifically appeal to children [12,13].A strong evidence base supports the association between exposure to unhealthy foods and a negative impact on children's dietary attitudes, preferences, and consumption [9][10][11]14]. Research in Canada and other economically developed countries has also shown that food and beverage companies target children across multiple media, including print media (e.g., magazines), [15,16] television, [17] digital media (e.g., viewed in social media, on desktop computers, on smartphones, etc. ), [18][19][20][21] and out-of-home media (e.g., billboards, signs, transit shelters) [22] as well as other settings such as schools and retail environments [13,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Alan yazını incelediğimizde çocuk dergileri ile ilgili uluslararası ve ulusal birçok çalışmaya rastlamak mümkündür (Ağan, 2019;Aksüt, 2021;Alabaş ve Kamer, 2016;Alabay, Can, Kandemir ve Güney, 2018;Chapman, Fairchild & Morgan, 2014;Dedeoğlu vd., 2011;Gezmen, 2019;Kurniawan, Waluyo, Suwandi & Setiawan, 2018;Jones & Reid, 2009;Morrow & Lesnick, 2001;Rea, 2018;Sarıkaya, 2018;Yıldırım, 2020). Morrow ve Lesnick (2001), çocuk dergilerindeki eğitsel değerler isimli çalışmalarında, öğretmenlerin büyük çoğunluğunun sınıfında dergilerin yer aldığını ve ders içeriklerini hazırlarken sıklıkla bu dergilerden faydalandıklarını bulgulamıştır.…”
Section: Introductionunclassified
“…While the extent of food advertising to children on television has been a focus of several studies worldwide (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) , including Slovenia (31) , the advertising of foods in children's and teens' magazines (CTM) has received much less attention (32) . While risks of misleading advertising exist in all types of media, such risks are of great concern in print media where the line between editorial content and advertising can be quite blurred (11,33,34) . This makes children even more vulnerable to the effects of advertising as they are typically unable to properly distinguish editorial and marketing content (35) .…”
mentioning
confidence: 99%